Thanks for the help everyone. It is in fact much simpler than I thought, here is my solution.
Since \(\displaystyle x^2\, +\, px\, +\, 1\) is a factor of \(\displaystyle ax ^3\, +\, bx\, +\, c\) , and since the other factor must be linear, in the form \(\displaystyle ax\, +\, c\), then we have:
. . . . .\(\displaystyle ax^3\, +\, bx\, +\, c\, =\, ax^3\, +\, (ap\, +\, c)\, x^2\, +\, (cp\, +\, a)\, x\, +\, c\)
Subtracting the first and last terms from either side, we get:
. . . . .\(\displaystyle bx\, +\, c\, =\, (ap\, +\, c)\,x^2\, +\, (cp\, +\, a)\, x\)
The first equation says that \(\displaystyle ap\, +\, c\, =\, 0\) and \(\displaystyle cp\, +\, a\, =\, b.\) This says that \(\displaystyle c\, =\, -ap\) so \(\displaystyle -\frac{c}{a}\, =\, p.\)
Plugging this into the second equation, we get:
. . . . .\(\displaystyle c\, \left(-\frac{c}{a}\right)\, +\, a\, =\, b\)
. . . . .\(\displaystyle -\frac{c^2}{a}\, +\, a\, =\, b\)
. . . . .\(\displaystyle -\frac{c^2}{a}\, +\, \frac{a^2}{a}\, =\, b\)
. . . . .\(\displaystyle \frac{a^2\, -\, c^2}{a}\, =\, b\)
Multiplying through, we get:
. . . . .\(\displaystyle a^2\, -\, c^2\, =\, ab\)
Or, using long division, we get a remainder of:
. . . . .\(\displaystyle (b\, -\, a\, +\, ap)\, x\, +\, (ap)\, 1\, =\, 0\)
The only way this equality is true for all values of \(\displaystyle x\) is if each of the parentheticals on the left-hand side is equal to zero. The second parenthetical says:
. . . . .\(\displaystyle ap\, =\, 0\)
We are given that \(\displaystyle a\, \neq\, 0,\), so it must be that \(\displaystyle p\, =\, 0.\) Plugging this into the other parenthetical, we get:
. . . . .\(\displaystyle b\, -\, a\, +\, 0\, =\, 0\)
. . . . .\(\displaystyle b\, =\, a\)
When we did the long polynomial division, the factor across the top of the division was:
. . . . .\(\displaystyle ax\, -\, ap\, =\, a(x\, -\, p)\)
But since \(\displaystyle p\, =\, 0,\) we really had a complete factorization in the form of:
. . . . .\(\displaystyle ax\, (x^2\, +\, 1)\, =\, ax^3\, +\, ax\, =\, ax^2\, +\, bx\, +\, c\)
This tells us that \(\displaystyle c\, =\, 0.\) Since \(\displaystyle a\, =\, b,\) then \(\displaystyle a\, -\, b\, =\, 0\, =\, c\). Squaring both sides of this gives us:
. . . . .\(\displaystyle a^2\, -\, 2ab\, +\, b^2\, =\, c^2\)
. . . . .\(\displaystyle a^2\, -\, c^2\, =\, 2ab\, -\, b^2\)
But \(\displaystyle a\, =\, b,\) so \(\displaystyle b^2\, =\, ab\) and:
. . . . .\(\displaystyle a^2\, -\, c^2\, =\, 2ab\, -\, ab\, =\, ab\)